Analisis Pasar Dan Pemasaran Produk Di CV. Kampoeng Roti Surabaya: Laporan Kegiatan Pengabdian Masyarakat - Erwin Tri Kurniyanto; I Gede Wiyasa (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The increase in the establishment of bakeries in various places is the result of increasing market demand. The development of the bread business in Indonesia continues to experience growth. Both small, medium and large businesses. Both in the form of industry and home businesses, whether from within the country or franchised from abroad. Likewise the supporting industries, such as machines, supporting materials and raw materials such as flour. The increasing number of bakeries mushrooming around Surabaya and East Java has changed people's mindset towards consuming bread every day which contains lots of nutrients and is good for health. Every company must try and be able to compete to survive and win the current competition. There are many ways that companies can do to increase consumer satisfaction and loyalty, for example by paying attention to price factors. Most consumers will tend to choose companies that offer relatively cheap product prices. Price is an important consideration for consumers when buying products from a company. Prices are not just the numbers printed on the price tag. Prices take many forms and perform many functions. Price is one element of the marketing mix that generates revenue, other elements generate costs. Price is perhaps the easiest element in a marketing program to adjust. Apart from price, product quality also greatly influences the success and progress of a business venture. Companies that are able to produce high quality products will be more profitable than producing low quality products. This means that consumers will be willing to buy a product at a reasonable or relatively affordable price with good product quality